Control previo y la gestión de tesorería de una municipalidad en Iquitos 2024 - García Pizango, Sandra (2025)
This research addresses the influence of ex ante control on the treasury management of a municipality in Iquitos in 2024, posing the central problem: how does ex ante control influence treasury management? Specific objectives were established to determine the impact of ex ante control on the dimensions of expenditure execution, file verification and payment management. The methodology used is based on a quantitative approach, with a non experimental cross-sectional design, applying questionnaires to a sample of civil servants and employees of the municipality. The results reveal that prior control has a direct and significant impact on treasury management, showing that its implementation improves expenditure execution (p=0.001), optimises file verification (p=0.002) and strengthens payment management (p=0.003). The findings suggest that more rigorous ex ante control not only contributes to efficiency and effectiveness in treasury management, but also promotes transparency and accountability in public administration. The research highlights the importance of establishing clear procedures and the need for staff training to maximise the use of public resources, thus benefiting the wider community.